METHODOLOGICAL ASPECTS OF CREATING AND USING AN ELECTRONIC TEXTBOOK OF POLYMER CHEMISTRY (World Bulletin of Social Sciences, 2024)
In the article, teaching based on 3D technologies, Augment realityAugment reality (AR), Virtual reality Virtual reality (VR), Mixed reality Mixed reality (MR), programs focused on effectiveness in teaching chemistry.